(3GdOQQ GdefKhQI aj HjGf RHO GdYdhe GdeTghQIs - (3YHO GdhgGH Hf CMeO Hf Ydj GdnMnfaj, fSHg Edi eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO , J (B973 (3g`s
(3ChdgG (B:s
(3hHYO adeG QCjJ GdfGS bO bUQJ geege ai MaX eJhf GdcJH Yf XgQ bdH s
(3BNQgG (B:s
(3eG ddgh eG GSJefi eGd GdYLR ef TjeI GdcjGS s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B469s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdeYGQa GdYGeIs